1971
DOI: 10.1210/endo-89-4-1024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orchiectomy on Pituitary Secretion of ACTH

Abstract: The effects of prepuberal gonadectomy on pituitary secretion of ACTH were studied in adult male rats. Plasma concentration of ACTH in unstressed adrenalectomized rats was increased following orchiectomy to 197% (95% confidence limits 134-289%) of the control level. Higher plasma ACTH concentrations were also observed in castrated animals with adrenals intact after the acute stress of ether anesthesia when compared to similarly stressed controls (159%; 121-215%). In both experiments, replacement with testostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 0 publications
5
21
0
Order By: Relevance
“…This in crease in CRH in the GDX male rat correlates with the increased CORT and ACTH response to physical and psychological stressors previously observed in the GDX male rat [15,16] and suggests that this pool of CRH is readily releasable. Although a previous study suggested that prepuberal gonadectomy of male rats did not affect the hypothalamic content of corticotropin-releasing bioactivity [20], our data are consistent with a more recent study showing increases in hypothalamic CRH peptide levels following long-term castration [21]. Also consistent with this study, we report here that more than 10 days are necessary to see an effect of castration on hypothalamic CRH content.…”
Section: Discussionsupporting
confidence: 93%
“…This in crease in CRH in the GDX male rat correlates with the increased CORT and ACTH response to physical and psychological stressors previously observed in the GDX male rat [15,16] and suggests that this pool of CRH is readily releasable. Although a previous study suggested that prepuberal gonadectomy of male rats did not affect the hypothalamic content of corticotropin-releasing bioactivity [20], our data are consistent with a more recent study showing increases in hypothalamic CRH peptide levels following long-term castration [21]. Also consistent with this study, we report here that more than 10 days are necessary to see an effect of castration on hypothalamic CRH content.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, many lines of evidence indicate that the reactivity of pituitary corticotropes to CRF may play a decisive role in the appearance of sex differences in the response to ether stress. In fact, it has been demonstrated that in vivo CRFinduced ACTH release is depressed in ovariectomized as well as in testosterone-treated rats [5,6,24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the decline in type I isozyme activity in response to adrenalectomy and hypophysectomy, coupled with the failure of prostate and levator ani to respond to adrenalectomy, would support the concept of adrenal steroids contributing to the maintenance of kinase pools in the liver. A direct effect of androgens cannot be ruled out but work by other authors suggests that, although ACTH production in male rats increases after orchiectomy (25), castration has a direct effect on adrenocorticoid secretion by acting to increase 5a-reductase activity in the adrenal cortex, resulting in lowered levels of corticosterone and increased conversion to the 5a-reduced metabolites 5a-dihydrocorticosterone and 3#,,5a-tetrahydrocortisone (26). Therefore, the change in adrenal metabolism may be the important component in the decrease in kinase pools seen on castration.…”
Section: Methodsmentioning
confidence: 98%